ПСЕВДОНИМИТЕ, ИНИЦИЈАЛИТЕ И АНОНИМИТЕ ВО МАКЕДОНСКАТА КНИЖЕВНОСТ ОД ПРВАТА ПОЛОВИНА НА XX ВЕК - Славчо Ковилоски (My University, 2025)
This study deciphers and analyses Macedonian literary pseudonyms from the first half of the 20th century. During this period, the development of Macedonian literature occurred under different conditions compared to the previous century, with some Macedonian authors also belonging to other literary traditions. Consequently, when discussing Macedonian pseudonyms in the first half of the 20th century, emphasis is placed on the interwar period. The artistic merit of Macedonian literary works from this time increased despite various political, ideological, and economic pressures which necessitated the use of pseudonyms. Several authors who employed pseudonyms are now considered foundational to contemporary Macedonian literature, including Kočo Racin, Angel Žarov, Venko Markovski, Gjorgji Abadžiev, and Kole Nedelkovski. By understanding pseudonyms, the Macedonian literature is enriched and increases in quantity and quality. Therefore, we emphasize the importance of such studies.
Keywords: pseudonyms; initials; anonyms; Macedonian literature in the first half of the 20th century; Macedonian literary circle